TRP channel expression correlates with the epithelial–mesenchymal transition and high-risk endometrial carcinoma - Van den Eynde, Charlotte; De Clercq, Katrien; Van Bree, Rieta; Luyten, Katrien; Annibali, Daniela; Amant, Frédéric; Han, Sileny; Van Nieuwenhuysen, Els; Baert, Thaïs; Peeraer, Karen; Voets, Thomas; Van Gorp, Toon; et al. (Cellular and molecular life sciences : CMLS, 2022)
Transient receptor potential (TRP) channels excel in cellular sensing as they allow rapid ion influx across the plasma membrane in response to a variety of extracellular cues. Recently, a distinct TRP mRNA expression signature was observed in stromal cells (ESC) and epithelial cells (EEC) of the endometrium, a tissue in which cell phenotypic plasticity is essential for normal functioning. However, it is unknown whether TRP channel mRNA expression is subject to the phenotypic switching that occurs during epithelial to mesenchymal transition (EMT) and mesenchymal to epithelial transition (MET), and whether TRP channel mRNA expression is associated with aggressive phenotypes in endometrial cancer (EC). Here, we induced EMT and MET in vitro using in primary EEC and ESC, respectively, and analyzed expression and functionality of TRP channels using RT-qPCR and intracellular Ca 2+ imaging. The outcome of these experiments showed a strong association between TRPV2 and TRPC1 mRNA expression and the mesenchymal phenotype, whereas TRPM4 mRNA expression correlated with the epithelial phenotype. In line herewith, increased TRPV2 and TRPC1 mRNA expression levels were observed in both primary and metastatic EC biopsies and in primary EC cells with a high EMT status, indicating an association with an aggressive tumor phenotype. Remarkably, TRPV2 mRNA expression in primary EC biopsies was associated with tumor invasiveness and cancer stage. In contrast, increased TRPM4 mRNA expression was observed in EC biopsies with a low EMT status and less aggressive tumor phenotypes. Taken together, this dataset proved for the first time that TRP channel mRNA expression is strongly linked to cellular phenotypes of the endometrium, and that phenotypic transitions caused by either experimental manipulation or malignancy could alter this expression in a predictable manner. These results implicate that TRP channels are viable biomarkers to identify high-risk EC, and potential targets for EC treatment.